Correlation between serum and liver levels of some adipokines and oxidative parameters in obese adult male rats with and without antioxidant - Mohammad M El-Shawwa (Wolters Kluwer Medknow Publications, 2019)
Background Obesity is associated with insulin resistance (IR), type 2 diabetes, dyslipidemia, and cardiovascular diseases. Apelin and chemerin were identified as adipose tissue markers. Several adipokines are known to influence food intake, including apelin, whose expression is regulated by insulin and chemerin. Because oxidative stress (OS) is involved in the complications associated with obesity, the antioxidant activity of Lepidium sativum may be of benefit, as L. sativum showed maximum antioxidant activity by inhibiting hazardous effects of many oxidants. Objective To clarify the pathophysiology of obesity by studying the nature of correlation between serum and liver levels of apelin and chemerin and oxidative parameters in obese rats with and without antioxidant. Materials and methods A total of 30 adult male albino rats were divided into three equal groups: group I was control, group II received high-fat diet (HFD), and group III received HFD as well as L. sativum. At the end of the experiment, blood samples were collected for estimation of the serum levels of chemerin, apelin, fasting glucose, insulin, IR, lipid profile, glutathione (GSH) and malondialdehyde (MDA). Levels of MDA, catalse (CAT), chemerin and apelin were estimated in liver homogenate. Results After 8 weeks, HFD group showed a significant increase in serum levels of apelin, chemerin, fasting glucose, insulin, IR, total cholesterol, very low-density lipoprotein, triglycerides, low-density lipoprotein cholesterol, and MDA and a significant decrease in high-density lipoprotein cholesterol and GSH. HFD also caused a significant increase in the tissue levels of MDA, CAT, and chemerin with a significant decrease in apelin, compared with control group. However, addition of L. sativum to HFD caused a significant decrease in serum levels of apelin, chemerin, fasting glucose, insulin, IR, total cholesterol, very low-density lipoprotein, triglycerides, low-density lipoprotein cholesterol, and MDA and a significant increase in high-density lipoprotein cholesterol and GSH. L. sativum also caused a significant decrease in tissue levels of MDA, chemerin, and CAT and a significant increase in apelin, compared with HFD group. Conclusion This study showed a significant positive correlation between liver and serum chemerin and between liver and serum MDA. On the contrary, it showed a significant negative correlation between liver and serum apelin as well as between liver CAT and serum GSH.